Instructional Methods and Hybrid Learning in Preservice Teacher Education—Case Studies in Portugal and Spain - Rodrigues, Ana Luísa (2022)
The preservice teacher education assumes a predominant role in the quality of the educational process that must be assumed in public education policies, noting the importance of reflection on a variety of aspects, including the curriculum, teaching and learning methods, and pedagogical practices. To this end, this article aims to: i) present and compare the curriculum and study plans of two preservice teacher education programs in Portugal and Spain; ii) study the instructional methods used and hybrid learning format in these programs in pandemic time; and iii) analyze how their pedagogical practices are developed in post-pandemic time, particularly about the use of digital technologies and online education. As result, it is intended to obtain a characterization of the Masters of access to the teaching profession and analyze the way their curricula and instructional methods are developed. We also intend to draw conclusions about the effects of the Covid-19 pandemic on pedagogical practices, namely regarding how technologies can enable motivation, facilitate learning, and have a positive influence on pedagogical practices.